2017
DOI: 10.1021/acs.jpcc.7b07186
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Enhanced Raman Spectroscopy of Acetil-neuraminic Acid on Silver Nanoparticles: Role of the Passivating Agent on the Adsorption Efficiency and Amplification of the Raman Signal

Abstract: We present a combined experimental and theoretical study dedicated to analyzing the surface-enhanced Raman spectra of solutions of citrate-covered silver nanoparticles (NPs) in the presence of acetil-neuraminic acid (Neu5Ac). The Raman signals from Neu5Ac (particularly the bands located at 1002 and 1237 cm −1 ) can easily be detected for concentrations as low as 1 mg/dl, providing outstanding molecular sensing properties for our synthesized Ag-NPs. When compared to its solid phase, Neu5Ac adsorption on citrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 31 publications
(55 reference statements)
2
9
0
Order By: Relevance
“…Some papers exclude K 1 (NG) and construct the reaction–diffusion equations by taking only K 2 (NG) into account. , The assumption that K 1 (NG) is not essential to the appearance of Liesegang patterns was validated in an experiment based on a reduction reaction that essentially excludes K 1 (NG) . The important role of K 2 (NG) in this system was clarified through experimental and numerical control of the nucleation energy based on surface chemistry in which the surface energy of nuclei or small clusters is controlled by an appropriate surface ligand . In such systems, the decrease in the spacing coefficient in the presence of the ligand is reproduced by the reaction-diffusion equation with reduced K 2 (NG) .…”
Section: Models Of Liesegang Pattern Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…Some papers exclude K 1 (NG) and construct the reaction–diffusion equations by taking only K 2 (NG) into account. , The assumption that K 1 (NG) is not essential to the appearance of Liesegang patterns was validated in an experiment based on a reduction reaction that essentially excludes K 1 (NG) . The important role of K 2 (NG) in this system was clarified through experimental and numerical control of the nucleation energy based on surface chemistry in which the surface energy of nuclei or small clusters is controlled by an appropriate surface ligand . In such systems, the decrease in the spacing coefficient in the presence of the ligand is reproduced by the reaction-diffusion equation with reduced K 2 (NG) .…”
Section: Models Of Liesegang Pattern Formationmentioning
confidence: 99%
“…55 The important role of K 2 (NG) in this system was clarified through experimental and numerical control of the nucleation energy 56 based on surface chemistry in which the surface energy of nuclei or small clusters is controlled by an appropriate surface ligand. 57 In such systems, the decrease in the spacing coefficient in the presence of the ligand is reproduced by the reaction-diffusion equation with reduced K 2 (NG) . This behavior can be explained through an interaction between ligand and nuclei in which the presence of the ligand reduces E c and K 2 (NG) and kinetically promotes the nucleation process during fluctuations between loosely interacting molecules and defined nuclei.…”
Section: ■ Introductionmentioning
confidence: 99%
“… 14 The use of SERS in biological fields has been widely reported. 15 , 16 Recently, SERS has been employed to detect the influenza virus and hepatitis B virus in human plasma. 17 19 However, the absence of clinical research makes it difficult for the practical applications of SERS in large-scale screening for SARS-CoV-2.…”
mentioning
confidence: 99%
“…It should be noted that trisodium citrate was applied as an additional stabilizing agent during the synthesis of AAgNPs (Section 2). Hernández‐Arteaga et al (2017) have discussed the Raman bands for the AgNPs covered by this reagent. According to the cited authors, the most intense signals due to citrate vibrations are observed at 924, 1125, 1399, and 1606 cm −1 .…”
Section: Resultsmentioning
confidence: 99%
“…Table S1. The wavenumbers and suggested band assignments for the Raman and SERS spectra of AA, GA and AAgNPs and GAAgNPs, respectively (Alvarez‐Ros et al, 2003; Boca et al, 2012; Garrido et al, 2016; Hernández‐Arteaga et al, 2017; YohannanPanicker et al, 2003). Table S2 .…”
mentioning
confidence: 99%